Capacitación científica y actividades de la red. América Central - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
In 1985 the Bean Project for Central America and the Caribbean, including tropical Mexico and Panama, continued to generate technology for national programs. On-farm trials and planting of nurseries were increased in each country; this resulted in the identification of promising materials superior to those which are presently in use. Good progress was made in incorporating resistance to apion godmani and in increasing the levels of resistance to BGMV, web blight, and common bacterial blight. Training was also increased through regional courses, in-country courses, and workshops. (CIAT)